1998
DOI: 10.1037/0022-0663.90.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated learning in high-achieving students: Relations to advanced reasoning, achievement goals, and gender.

Abstract: We express our gratitude to Sylvia Fernandez-Fein and Heinrich Stumpf for their valuable comments on earlier drafts of this article. We also thank Valerie Hoffhines for endless hours of coding and data entry. Of course, we thank the participants for sharing information about themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
94
3
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(135 citation statements)
references
References 32 publications
15
94
3
14
Order By: Relevance
“…Additionally, higher scores were reported by girls on the scales product evaluation and process evaluation. These results generally confirm findings from previous research (e.g., Ablard & Lipschultz, 1998;Vandevelde et al, 2013;Wall, Higgins, Remedios, Rafferty, & Tiplady, 2013;Zimmerman & Martinez-Pons, 1990). However, Vandevelde et al (2013) did not find any significant differences between boys and girls for process evaluation.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…Additionally, higher scores were reported by girls on the scales product evaluation and process evaluation. These results generally confirm findings from previous research (e.g., Ablard & Lipschultz, 1998;Vandevelde et al, 2013;Wall, Higgins, Remedios, Rafferty, & Tiplady, 2013;Zimmerman & Martinez-Pons, 1990). However, Vandevelde et al (2013) did not find any significant differences between boys and girls for process evaluation.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…It has been reported that boys are less motivated than girls and spend less time doing homework and that boys have lower expectations of themselves and are less enthusiastic about continuing their studies (Barber, 1996;Cox, 2000;Darom & Rich, 1988;Hatzichristou & Hopf, 1996;Warrington et al, 2000). As for the cognitive dimension of student engagement, there is also evidence showing that girls are more likely than boys to plan, monitor, and regulate their cognitions and study activities (Ablard & Lipschultz, 1998;KenneyBenson, Pomerantz, Ryan, & Patrick, 2006;Patrick, Ryan, & Pintrich, 1999;Zimmerman & Martinez-Pons, 1990). On the basis of the extant evidence, one may speculate that the gender differences in student engagement might influence gender differences in academic performance.…”
Section: Gender Considerationsmentioning
confidence: 99%
“…In the research, it has seen that the self-regulation skills of gifted students are higher than non-gifted students. It is known that gifted students are a self-employed (autonomy) individual who has motivated himself/herself and manages his/her own learning (that s/he uses self-regulated learning (Clark, 1992;Risemberg & Zimmerman, 1992;Heller, 1999;Zimmerman & MartinezPons, 1990;Ablard & Lipschultz, 1998).…”
Section: Discussionmentioning
confidence: 99%